HUBUNGAN EFIKASI DIRI BIDANG AKADEMIK DAN PERILAKU BELAJAR DENGAN HASIL BELAJAR GEOGRAFI KELAS XI IS DI MAN 3 BANDA ACEH - Susi Suriyani; Abdul Wahab Abdi; . Hasmunir (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2017)
Self  efficacy  is  very  important  in  the  daily  life  of  students  because  it  can build a sense of confidence, student motivation, and as a reflection of each individual about the ability to learn in every field of learning. Students with good or bad self efficacy can also influence students' behavior in the learning process. The problem formulation in this research is whether there is a significant correlation between self efficacy of academic field and learning behavior with learning result of class XI IS geography  in  MAN  3  Banda  Aceh.  In  particular  this  study  aims  to  determine  the relationship between self-efficacy academic field and learning behavior with learning outcomes geography class XI IS in MAN 3 Banda Aceh. This  research  approach  is  a  quantitative  approach.  The  population  of  this study  were  students  of  MAN  3  Banda  Aceh,  while  the  sample  in  the  study  were students of class XI IS MAN 3 Banda Aceh. Based  on  data  analysis,  the  findings  of  this  study  can  be  put  forward  as follows:  the  relationship  between  self-efficacy  in  the  academic  field  (X1)  and learning behavior (X2) with the learning outcomes of geography (Y) class XI IS in MAN  3  Banda  Aceh  is  0.136  very  low.  The  correlation  between  self efficacy of academic  field (X1), learning behavior (X2), and geography learning result (Y) has no  significant  relation  with  value  of  Fcount  and  Ftable  ie  0,366  3,24.  The conclusion  of  this  research  is  that  there  is  no  significant  correlation  between  self efficacy of academic  field and learning behavior with learning result of class XI IS geography in MAN 3 Banda Aceh